Hints for the busy housewife (London : Health & Cleanliness Council)
1939-05 1939 1930s 50 pages : illustrations HINTS FOR THE BUSY HOUSEWIFE room. Provide yourself with a can of hot water, a jug of cold, and a cake of really good toilet soap, and wash your body bit by bit while you stand in a foot-bath or even in the hand-basin. It is well worth while to take this extra bit of trouble to be really clean. 2. CARE OF THE HANDS You are in danger when your hands are dirty. Dirt is the lurking-place of germs. You may infect everything you touch — food, clothes, your mouth and nose. The slightest prick or scratch may be an opening through which disease germs can enter and set up blood-poisoning. Your safeguard is cleanliness. When you are on a very dirty job cover the hands with a "dry" thick lather of soap, letting it get under the nails. When you wash them after the job, the dirt will come away quickly and easily. People who work in gardens or stables must pay great attention to cleanliness, for the germs of lockjaw (as well as those of other diseases) lurk in these places and can get into the body through any cut, scrape or scratch. [photograph] Pressing back the cuticle. Never prepare food, set a table, or take a meal with dirty hands, for they will contaminate Page Thirty-three 177/5/8/1